The stranger in the lifeboat [large type] : a novel - Albom, Mitch, 1958- (Harper Large Print, an imprint of HarperCollinsPublishers, 2021)
After a deadly ship explosion, nine people, adrift in a raft, struggle to survive at sea and pull a strange man from the sea who claims to be the Lord.